ANALISIS PENGELOLAAN DANA HAJI PADA MASA PANDEMI COVID 19 PADA KEMENTRIAN AGAMA DI KOTA JAMBI - Fitri Ayu Santika; Usdeldi Usdeldi; Eri Nofriza (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This research is entitled Analysis of Hajj Fund Management During the Covid 19 Pandemic at the Ministry of Religion in Jambi City. The research method used by researchers is a qualitative approach. The results of this research are: 1) Management of Hajj funds in the Ministry of Religion of Jambi City during the Covid 19 period, including: the Hajj fund manager receives Hajj funds from Jambi Province Hajj pilgrims, then the Hajj fund manager manages the Hajj funds, after that allocates the results of Hajj fund management These are for the various accommodation needs of the congregation. The use of Hajj funds in Kemanag, Jambi City during the Covid 19 period was used in 4 sectors, namely 1) Accommodation for pilgrims, 2) Operational costs for pilgrims and guidance for Hajj pilgrims. 3) Handling and anticipating handling of Covid 19 in the congregation. 4) Sharia investment in the form of Sukuk. 2) There are a number of obstacles faced in managing Hajj funds at the Jambi City Ministry of Religion during Covid 19. The obstacle faced by the Jambi City Ministry of Religion in obtaining Hajj funds is the lack of income from Hajj funds. This could happen because of Covid 19 and decreased congregational interest. Meanwhile, in terms of using Hajj funds, handling Covid for Hajj pilgrims, allocating Hajj Funds, monitoring Hajj Funds and managing Hajj funds, there are no significant obstacles. 3) The Jambi City Ministry of Religion has implemented sharia objectives of financial management in the form of religious protection or hifdz a-din. In a review of Islamic financial management, the use of Hajj funds at the Jambi City Ministry of Religion is able to meet life protection needs. Likewise in the case of hifdz al-aql or protection of reason. The Ministry of Religion of Jambi City is able to fulfill this need for intellectual protection. In terms of hifdz al-maal or protection of assets. The Ministry of Religion of Jambi City is also therefore able to fulfill these asset protection needs. However, in terms of hifdz al-nasl (protection of offspring/family), the Jambi City Ministry of Religion is not yet included in the category of hifdz al-nasl or family protection.